Tetraclinis articulata (vahl) masters: An insight into its ethnobotany, phytochemistry, toxicity, biocide and therapeutic merits - Khatib, Sohaib; Sobeh, Mansour; Bouissane, Latifa (Frontiers in Pharmacology, 2022)
Tetraclinis articulata (Vahl) Masters, commonly known as Sandarac and Araâr, is the only species representing the genus Tetraclinis Masters. The plant's usage could be traced back to 1800 B.C, wherein it has been extensively exploited for therapeutic, artistic, and ritual purposes. Recently, a full range of ethnobotanical investigations has been undertaken to document the plant's empirical knowledge. They reported the use of different parts, such as leaves, stems, cones, bark, and roots, as part of folk healing practices to manage diabetes mellitus, hypertension, fever, stomach disorders, and diarrhea, among others. An extensive literature-based search was performed using various online databases, including ScienceDirect, PubMed, Google Scholar, Scopus, Springer, ResearchGate, to retrieve up-to-date information regarding taxonomy, edaphic and pedoclimatic conditions, geographical distribution, ethnobotany, photochemistry, pharmacological activities, and biocide properties of T. articulata (Vahl) Masters. Likewise, various books containing botanical and ethnopharmacological information were consulted. Moreover, given the scarcity of toxicological research on the plant species and its major constituents, we have relied on the online web tool ProTox-II (http://tox.charite.de/protox_II) to predict the in silico toxicity of phenolic compounds as well as the main volatile compounds detected in T. articulata. To date, at least 130 compounds have been isolated or analytically characterized in T. articulata leaves, cones, resin, bark, and woods. These chemical constituents are categorized into phenolic acids, flavonoids and their derivatives, volatile compounds, phytosterols, and fatty acids, among others. These bioactive agents have strongly been correlated with the significant antimicrobial, antioxidant, neuroprotective, antiurolithiatic, anti-inflammatory, antidiabetic, and cytotoxic properties of the plant-based extracts and isolated components. Toxicological studies argued that the plant is quite safe and devoid of eventual toxicity. However, in-depth investigations are required to validate the safety of the plant. On the other hand, the remarkable antimicrobial potency of various extracts from the plant against a wide range of foodborne pathogens supports their possible use to increase the shelf life of foodstuffs and as natural flavoring agents in the Agri-food industry. Likewise, various plant-based extracts have been proven to exert substantial biocidal properties, making them potential alternatives to synthetic pesticides in agriculture.